Dynamic Adaptation in Child–Adult Language Interaction. Issue 2 (5th March 2013) - van Dijk, Marijn; van Geert, Paul; Korecky‐Kröll, Katharina; Maillochon, Isabelle; Laaha, Sabine; Dressler, Wolfgang U.; Bassano, Dominique
Abstract : When speaking to young children, adults adapt their language to that of the child. In this article, we suggest that this child‐directed speech (CDS) is the result of a transactional process of dynamic adaptation between the child and the adult. The study compares developmental trajectories of three children to those of the CDS of their caregivers. Furthermore, a mathematical‐conceptual model is built that captures the essential dynamics of adaptation in a series of coupled equations. This model is sensitive to changes in the language development of the child. The results show evidence for a dynamic form of adaptation, although there are also clear individual differences.